REVEALING GHOST BUSINESS-TO-BUSINESS CLIENTS THROUGH GOSH’S MODEL. A CHALLENGE FOR EU LEISURE AND ENTERTAINMENT ACTIVITIES - Droli, Maurizio; Margherita Chang, Ting Fa; Iseppi, Luca (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The concept of intermediate market trade contacts (ITC) have been developed as transactional capital resource measured by business-to-business purchases or sales. In the framework of the resource-based view, only valuable, rare, inimitable and non-substitutable firm's resources might be considered as a source of sustained competitive advantage. Supplydriven Ghosh's model has been applied to Eurostat symmetric input-output tables of 23 EU countries. A strong and direct relationship between market horizontal multiplier for productive use and indirect ITC frequency has been found for recreational, cultural and sporting activities. Consequently, valuable and distinct hidden-client purchases could be used as a resource favoring firm development, innovation and territorial integration strategies.